MEMAHAMAMI PROSES ADAPTASI MAHASISWA TORAJA DI SEMARANG - Agnes Sarung Allo; Hedi Pudjo Santoso (Interaksi Online, 2019)
Life of shoreline students in the process of adaptation is interested to be researched, considering that there are many issues they may face during adapting process, such as how they overcomenee culture. Toraja students studying in Semarang become the main focus of this research regarding how they go throught with process of adaptation in new environment. The object of this research is to examine the experience of Toraja students in adapting life in Semarang. It conducts descriptive qualitative method with terminological approach. In addition, the theory of Culture Shock (U-Curve) Gundykunst dan Kim (2010), is applied in order to help the researcher explan the findings. This research takes three Torajanese students as the object of research. The research focuses on four phases, namely; Phase of Joy; Disappointment Phase; Phase of Resolution and Phase Functions Effectively. This research took three students from Toraja. The findings show that Toraja students studying at earlier phase studying in Semarang experience the excitement and have good college life expectation in new environment. The results of this study indicate that Toraja students who are educated in Semarang Toraja students feel happy and have hope for college life in a new environment. After adapting, Toraja students experience a culture shock because of the cultural differences espoused specifically in understanding language differences and habits in the living environment. The last is Toraja students after going through the phases in the adaptation process where Toraja students begin to be able to socialize well with the campus environment and place of residence and begin to adopt several cultures in new environments such as using regional languages.